Peran Kepemimpinan dalam Kolaborasi Jaringan pada SMPN 6 Meureubo untuk Meningkatkan Kualitas Pendidikan - Seprida, Seprida; Aripin, Nurasma (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This research aims to describe the role of leadership in network collaboration at SMPN 6 Meureubo for improving the quality of education. A descriptive approach is used to illustrate the phenomena in the field regarding the role of the school principal in enhancing the quality of education through collaboration with various parties (network collaboration). Informants were chosen based on purposive sampling, which means that all informants interviewed are members of SMPN 6 Meurebo, such as teachers, educational staff, and the school principal. The results of the study indicate that resource management, curriculum development, and communication with parents and the community are important parts of the principal's leadership. The main findings show that network collaboration allows for resource optimization and strengthening educational support. This research contributes to the development of school leadership and the improvement of educational quality.